2016
DOI: 10.1002/hbm.23159
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure and impulsivity in methamphetamine dependence with and without a history of psychosis

Abstract: MAP patients show distinct patterns of impaired white matter integrity of global nature relative to controls and the MA group. Future work to investigate the precise nature and timing of alterations in MAP is needed. The results are further suggestive of frontal white matter pathology playing a role in impulsivity in MA dependence and MAP. Hum Brain Mapp 37:2055-2067, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
5
23
1
Order By: Relevance
“…Mean diffusivity has been correlated with the intercellular space and compactness of white matter, and greater mean diffusivity values were significantly correlated with negative psychotic symptoms in the study (Uhlmann, Fouche, Lederer, et al, ). High levels of self‐report impulsivity was associated with decreases in regional frontal white matter integrity measures in both MAP and methamphetamine users without psychosis (Uhlmann, Fouche, Lederer, et al, ). Another study found significant colinear relationships between serum protein levels and diffusion tensor imaging markers (i.e., white matter measures) in healthy controls that was disrupted in MAP and MA users (Breen et al, ).…”
Section: Biological Basis Of Mapmentioning
confidence: 66%
See 2 more Smart Citations
“…Mean diffusivity has been correlated with the intercellular space and compactness of white matter, and greater mean diffusivity values were significantly correlated with negative psychotic symptoms in the study (Uhlmann, Fouche, Lederer, et al, ). High levels of self‐report impulsivity was associated with decreases in regional frontal white matter integrity measures in both MAP and methamphetamine users without psychosis (Uhlmann, Fouche, Lederer, et al, ). Another study found significant colinear relationships between serum protein levels and diffusion tensor imaging markers (i.e., white matter measures) in healthy controls that was disrupted in MAP and MA users (Breen et al, ).…”
Section: Biological Basis Of Mapmentioning
confidence: 66%
“…Uhlmann (2016) Decreases in fractional anisotropy signal a general decrease in white matter integrity, and increased radial and axial diffusivity has been related to decreased myelination and axonal integrity, respectively (Breen et al, 2017). Mean diffusivity has been correlated with the intercellular space and compactness of white matter, and greater mean diffusivity values were significantly correlated with negative psychotic symptoms in the study (Uhlmann, Fouche, Lederer, et al, 2016). High levels of self-report impulsivity was associated with decreases in regional frontal white matter integrity measures in both MAP and methamphetamine users without psychosis (Uhlmann, Fouche, Lederer, et al, 2016).…”
Section: Imaging Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…3). Nevertheless, any claims that antipsychotic agents may be effective in countering methamphetamine-associated brain connectivity abnormalities needs to be considered in light of (1) extensive white matter microstructural abnormalities in MAP patients drawn from the same cohort as reported on in this paper (Uhlmann et al, 2016); (2) the observation that the effects of haloperidol on intrinsic functional brain connectivity and cognition are likely to be complex, involving both linear and non-linear changes that are region-dependent (Cole et al, 2013), with these effects depending on baseline levels of dopamine which are themselves influenced by factors such as patterns of methamphetamine use and individual genetic variability (Cools and D'Esposito, 2011);and (3), the observation that the relatively specific D1 receptor blocking action of haloperidol has actually been linked to the suppression of frontal lobe function (Harvey et al, 1999). Although the effect on network connectivity of duration of (1) methamphetamine abstinence and (2) treatment with antipsychotics was confounded in this study by the strong association between the latter factors (Spearman rho = 0.91), there was preliminary evidence that longer treatment rectified anomalous interactions between DMN and CCN intrinsic networks in MAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect on network connectivity of duration of (1) methamphetamine abstinence and (2) treatment with antipsychotics was confounded in this study by the strong association between the latter factors (Spearman rho = 0.91), there was preliminary evidence that longer treatment rectified anomalous interactions between DMN and CCN intrinsic networks in MAP patients. Nevertheless, any claims that antipsychotic agents may be effective in countering methamphetamine-associated brain connectivity abnormalities needs to be considered in light of (1) extensive white matter microstructural abnormalities in MAP patients drawn from the same cohort as reported on in this paper (Uhlmann et al, 2016); (2) the observation that the effects of haloperidol on intrinsic functional brain connectivity and cognition are likely to be complex, involving both linear and non-linear changes that are region-dependent (Cole et al, 2013), with these effects depending on baseline levels of dopamine which are themselves influenced by factors such as patterns of methamphetamine use and individual genetic variability (Cools and D'Esposito, 2011);and (3), the observation that the relatively specific D1 receptor blocking action of haloperidol has actually been linked to the suppression of frontal lobe function (Harvey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%